Acetylome in Human Fibroblasts From Parkinson's Disease Patients - Yakhine-Diop, Sokhna M. S.; Rodríguez-Arribas, Mario; Martínez-Chacón, Guadalupe; Uribe-Carretero, Elisabet; Gómez-Sánchez, Rubén; Aiastui, Ana; López de Munain, Adolfo; Bravo-San Pedro, José M.; Niso-Santano, Mireia; González-Polo, Rosa A.; Fuentes, José M. (Frontiers in Cellular Neuroscience, 2018)
Parkinson’s disease (PD) is a multifactorial neurodegenerative disorder. The pathogenesis of this disease is associated with gene and environmental factors. Mutations in leucine-rich repeat kinase 2 (LRRK2) are the most frequent genetic cause of familial and sporadic PD. Moreover, posttranslational modifications, including protein acetylation, are involved in the molecular mechanism of PD. Acetylation of lysine proteins is a dynamic process that is modulated in PD. In this descriptive study, we characterized the acetylated proteins and peptides in primary fibroblasts from idiopathic PD (IPD) and genetic PD harboring G2019S or R1441G LRRK2 mutations. Identified acetylated peptides are modulated between individuals’ groups. Although acetylated nuclear proteins are the most represented in cells, they are hypoacetylated in IPD. Results display that the level of hyperacetylated and hypoacetylated peptides are respectively enhanced in genetic PD and in IPD cells.